Kunitz trypsin inhibitor from chickpea (Cicer arietinum L.) that exerts anti-metabolic effect on podborer (Helicoverpa armigera) larvae - Srinivasan, A.; Giri, Ashok P.; Harsulkar, Abhay M.; Gatehouse, J. A.; Gupta, Vidya S. (Plant Molecular Biology, 2005)
Chickpea (Cicer arietinum L.) seeds contain Bowman-Birk proteinase inhibitors, which are ineffective against the digestive proteinases of larvae of the insect pest Helicoverpa armigera. We have identified and purified a low expressing proteinase inhibitor (PI), distinct from the Bowman-Birk Inhibitors and active against H. armigera gut proteinases (HGP), from chickpea seeds. N-terminal sequencing of this HGP inhibitor revealed a sequence similar to reported pea (Pisum sativum) and chickpea alpha-L-fucosidases and also homologous to legume Kunitz inhibitors. The identity was confirmed by matrix assisted laser desorption ionization - time of flight analysis of tryptic peptides and isolation of DNA sequence coding for the mature protein. Available sequence data showed that this protein forms a distinct phylogenetic cluster with Kunitz inhibitors from Glycine max, Medicago truncatula, P. sativum and Canavalia lineata. The isolated coding sequence was cloned into a yeast expression vector and produced as a recombinant protein in Pichia pastoris. alpha-L-fucosidase activity was not detectable in purified or recombinant protein, by solution assays. The recombinant protein did not inhibit chymotrypsin or subtilisin activity but did exhibit stoichiometric inhibition of trypsin, comparable to soybean Kunitz trypsin inhibitor. The recombinant protein exhibited higher inhibition of total HGP activity as compared to soybean kunitz inhibitor, even though it preferentially inhibited HGP-trypsins. H. armigera larvae fed on inhibitor-incorporated artificial diet showed significant reduction in average larval weight after 18 days of feeding demonstrating potent antimetabolic activity. The over-expression of this gene in chickpea could act as an endogenous source of resistance to H. armigera.
Keywords: Chickpea; Cicer arietinum; fucosidase; Helicoverpa armigera; Kunitz; Proteinase inhibitor

Response of trichogramma chilonis to infochemicals: an SEM and electrophysiological investigation - Sen, A; Raina, R; Joseph, Mary P.; Tungikar, VB (Biocontrol, 2005)
The external morphology and peripheral olfactory responses of antennal chemoreceptors of Trichogramma chilonis Ishii (Hymenoptera:Trichogrammatidae) to host related stimuli were examined by SEM and EAG technique respectively. The antennae of male and female T. chilonis reveal strong sexual dimorphism in structure as well as in types, density and distribution of individual sensillar types. The female antennae are characterized by the presence of a single uniporous sensilla on the apical tip of the dome and numerous multiporous pitted sensilla. Sensilla common to both males and females include the multiporous plate sensilla, the peg sensilla and trichoid sensilla. Differences between males and females occur with respect to their EAG profiles to 22 chemicals commonly found in plants viz., hexanal, β-pinene, citronellal, terpinene, citronellol, phytol, caryophyllene, R-(+)-limonene, linalool, carvacrol, cis-3-hexen-1-ol, ethanol, α-pinene, trans-2-hexanal, α-phellandrene, amyl acetate, cineole, quinolene, S-(-)limonene, β-myrcene, carvone, terpineol; hexane leaf extracts of three host plants of Helicoverpa armigera (cotton, chickpea and pigeon pea) and hexane scale extracts of adult males and females of H. armigera. Individually, the largest peak amplitudes in females were obtained with citronellal, phytol, caryophyllene, R-(+)-limonene, linalool, carvacrol and citronellol while in males citronellol, caryophyllene, linalool, R-(+)-limonene and amyl acetate caused the highest response. Among the different chemical classes, the largest peak amplitudes in females were obtained with oxygenated monoterpenes, while in males, fatty acid derivatives caused the highest response. In both males and females, the hydrocarbon monoterpenes caused the least response. Thus, the wide spectrum response of Trichogramma chilonis, to a wide group of chemicals belonging to different chemical classes, though varying, nevertheless suggests that using plant information enhances its parasitization efficiency.
Keywords: antennae; Chickpea; cotton; EAG; parasitoid; pigeon pea; scanning electron microscopy; Trichogramma chilonis; Volatiles

Differentially expressed gene transcripts in roots of resistant and susceptible chickpea plant (Cicer arietinum L.) upon Fusarium oxysporum infection - Nimbalkar, Suhas B.; Harsulkar, Abhay M.; Giri, Ashok P.; Sainani, Mohini N.; Franceschi, Vincent R.; Gupta, Vidya S. (Physiological and Molecular Plant Pathology, 2006)
Differentially expressed genes in chickpea, (Cicer arietinum L.) during root infection by Fusarium oxysportan f sp. ciceri Racel, were identified using cDNA-RAPD and cDNA-AFLP approaches. The former employed decamer primers on cDNA template and revealed nine differentially expressed transcripts in the resistant-infected chickpea variety. Among the 2000 transcript-derived fragments (TDFs) screened by cDNA-AFLP, 273 were differentially expressed in chickpea roots during Fusaritan infection. Only 13.65% of the TDFs were differentially regulated during pathogen challenge, while the other 86% were expressed non-differentially during the process of pathogen infection in chickpea roots. Nineteen TDFs, which expressed differentially in the resistant-infected chickpea variety were cloned and sequenced. Two of these TDFs were similar to transcription factors like WRKY proteins and 14-3-3 proteins, while three TDFs represented the NBS-LRR-type gene sequences. Two TDFs had sequence identity to genes known to have function in defense. The RAPID TDF CaFRi60 showed sequence identity to gamma-glutamyl-cysteine synthetase. Among the TDFs examined by cDNA-AFLP, 19 were confirmed by Reverse Northern blot to be differentially expressed. The data confirms the effectiveness of the cDNA-AFLP technique in detecting differentially expressed genes during pathogenesis. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cDNA-AFLP; Chickpea; Cicer arietinum; differentially expressed genes; fusarium oxysporum; Transcriptome

Chickpea Kunitz Inhibitor: a mechanistic basis for trypsin inhibition - Bendre, Ameya Dipak; Ramasamy, Sureshkumar; Suresh, C. G. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Chickpea; Kunitz Inhibitor; Protease

Metabolic profiling of chickpea-Fusarium interaction identifies differential modulation of disease resistance pathways - Kumar, Yashwant; Dholakia, Bhushan B.; Panigrahi, Priyabrata; Kadoo, Narendra Y.; Giri, Ashok P.; Gupta, Vidya S. (Phytochemistry, 2015)
Chickpea is the third most widely grown legume in the world and mainly used as a vegetarian source of human dietary protein. Fusarium wilt, caused by Fusarium oxysporum f. sp. ciceri (Foc), is one of the major threats to global chickpea production. Host resistance is the best way to protect crops from diseases; however, in spite of using various approaches, the mechanism of Foc resistance in chickpea remains largely obscure. In the present study, non-targeted metabolic profiling at several time points of resistant and susceptible chickpea cultivars using high-resolution liquid chromatography-mass spectrometry was applied to better understand the mechanistic basis of wilt resistance or susceptibility. Multivariate analysis of the data (OPLS-DA) revealed discriminating metabolites in chickpea root tissue after Foc inoculation such as flavonoids, isoflavonoids, alkaloids, amino acids and sugars. Foc inoculated resistant plants had more flavonoids and isoflavonoids along with their malonyl conjugates. Many antifungal metabolites that were induced after Foc infection viz, aurantion-obstine beta-glucosides and querecitin were elevated in resistant cultivar. Overall, diverse genetic and biochemical mechanisms were operational in the resistant cultivar for Foc defense as compared to the susceptible plant. The resistant chickpea plants employed the above-mentioned metabolic pathways as potential defense strategy against Foc. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chickpea; Fusarium wilt; LC-MS; Metabolomics; OPLS-DA; Phytoalexin

Fusarium oxysporum mediates systems metabolic reprogramming of chickpea roots as revealed by a combination of proteomics and metabolomics - Kumar, Yashwant; Zhang, Limin; Panigrahi, Priyabrata; Dholakia, Bhushan B.; Dewangan, Veena; Chavan, Sachin G.; Kunjir, Shrikant M.; Wu, Xiangyu; Li, Ning; Rajmohanan, Pattuparambil R.; Kadoo, Narendra Y.; Giri, Ashok P.; et al. (Plant Biotechnology Journal, 2016)
Molecular changes elicited by plants in response to fungal attack and how this affects plant-pathogen interaction, including susceptibility or resistance, remain elusive. We studied the dynamics in root metabolism during compatible and incompatible interactions between chickpea and Fusarium oxysporum f. sp. ciceri (Foc), using quantitative label-free proteomics and NMR-based metabolomics. Results demonstrated differential expression of proteins and metabolites upon Foc inoculations in the resistant plants compared with the susceptible ones. Additionally, expression analysis of candidate genes supported the proteomic and metabolic variations in the chickpea roots upon Foc inoculation. In particular, we found that the resistant plants revealed significant increase in the carbon and nitrogen metabolism; generation of reactive oxygen species (ROS), lignification and phytoalexins. The levels of some of the pathogenesis-related proteins were significantly higher upon Foc inoculation in the resistant plant. Interestingly, results also exhibited the crucial role of altered Yang cycle, which contributed in different methylation reactions and unfolded protein response in the chickpea roots against Foc. Overall, the observed modulations in the metabolic flux as outcome of several orchestrated molecular events are determinant of plant's role in chickpea-Foc interactions.
Keywords: Chickpea; fusarium oxysporum; Metabolomics; NMR; plant-pathogen interaction; proteomics

Structural insights into the unique inhibitory mechanism of Kunitz type trypsin inhibitor from Cicer arietinum L. Vol. 37 - Bendre, Ameya D.; Suresh, C. G.; Shanmugam, Dhanasekaran; Ramasamy, Sureshkumar (Journal of Biomolecular Structure & Dynamics, 2019)
Kunitz-type trypsin inhibitors bind to the active pocket of trypsin causing its inhibition. Plant Kunitz-type inhibitors are thought to be important in defense, especially against insect pests. From sequence analysis of various Kunitz-type inhibitors from plants, we identified CaTI2 from chickpea as a unique variant lacking the functionally important arginine residue corresponding to the soybean trypsin inhibitor (STI) and having a distinct and unique inhibitory loop organization. To further explore the implications of these sequence variations, we obtained the crystal structure of recombinant CaTI2 at 2.8 angstrom resolution. It is evident from the structure that the variations in the inhibitory loop facilitates non-substrate like binding of CaTI2 to trypsin, while the canonical inhibitor STI binds to trypsin in substrate like manner. Our results establish the unique mechanism of trypsin inhibition by CaTI2, which warrant further research into its substrate spectrum.
Keywords: Chickpea; crystal structure; inhibitory loop; Kunitz trypsin inhibitor; Trypsin

Functional stability and structural transitions of a kunitz trypsin inhibitor from chickpea (CaTI2) - Bendre, Ameya D.; Shukla, Ekta; Ramasamy, Sureshkumar (Protein Journal, 2020)
Enzymes are important tools for various applications. We have studied structural transitions and functional stability of a Kunitz trypsin inhibitor from Chickpea (CaTI2), a potent insect gut-protease inhibitor, under different stress conditions like non-neutral pH, elevated temperature and co-solvent concentrations. CaTI2 was cloned and expressed in an eukaryotic systemP. pastorisand was investigated for conformational transitions using circular dichroism spectroscopy, differential scanning fluorimetry and activity assay. Native CaTI2 has a sheet dominant structure with 40% beta sheets and possess a single tryptophan residue situated in the hydrophobic core of the enzyme. The recombinant inhibitor maintained its maximum activity under alkaline pH with its secondary structure intact between pH 6-10. CaTI2 was observed to be thermally stable up to 55 degrees C with aT(m) of 61.3 degrees C above which the protein unfolds. On treating with chemical denaturant (urea), the CaTI2 lost its inhibitory potential and native conformation beyond 2 M urea concentration. Moreover, the protein unfolded at lower temperatures as the concentration of denaturant increased, suggesting more complex structural changes. Further, the stability of the inhibitor was found to be directly proportional to the solvent polarity. The data, herein offers significant information of inhibitor stability and activity which could be exploited for its further development into an effective pesticide. [GRAPHICS] .
Keywords: Chickpea; Circular dichroism spectroscopy; Differential scanning fluorimetry; Functional stability; Kunitz trypsin inhibitor

Characterization of wound-induced electrical signals and reactive oxygen species in chickpea (Cicer arietinum) - Deshpande, Shweta; Pawar, Shivani; Kumari, Archana (Plant Signaling & Behavior, 2025)
Mechanical damage to plants triggers both localized and systemic responses that activate plant defense mechanisms. Early signaling events include calcium (Ca2+) flux, reactive oxygen species (ROS), and electrical alterations. These signals coordinate downstream defense pathways, enabling plant acclimation to biotic stress. Electrical signaling following wounding/herbivory has been extensively studied in Arabidopsis; however, its dynamics in crop plants such as chickpea (Cicer arietinum) are not well understood. The pattern of the SWP in chickpea was similar to that in Arabidopsis but with a longer repolarization phase and was detectable only within the leaflets. The signals generated by damaging the leaflet were more pronounced, propagated bidirectionally and varied between herbivore-susceptible and tolerant chickpea varieties. The SWP duration is correlated with increased expression of AOS and OPR3 transcripts, which are markers of the stress hormone JA. Additionally, ROS production in wounded chickpea leaflets is associated with increased expression of ROS-generating genes. The use of DPI, an inhibitor of NADPH oxidase, which is responsible for ROS production, inhibited SWP, suggesting the crucial role of ROS in wound-induced SWP. This study provides insight into the interplay between wound-induced electrical signaling and ROS production in chickpea and proposes the measurement of electrical signals as a rapid, noninvasive approach for screening crop cultivars for pest susceptibility and tolerance.
Keywords: Chickpea; Electrical signal; Plant defense; ROS; wound